2023
DOI: 10.1055/s-0043-1776782
|View full text |Cite
|
Sign up to set email alerts
|

Management of Brain Metastases: A Review of Novel Therapies

Shreyas Bellur,
Atulya Aman Khosla,
Ahmad Ozair
et al.

Abstract: Brain metastases (BMs) represent the most common intracranial tumors in adults, and most commonly originate from lung, followed by breast, melanoma, kidney, and colorectal cancer. Management of BM is individualized based on the size and number of brain metastases, the extent of extracranial disease, the primary tumor subtype, neurological symptoms, and prior lines of therapy. Until recently, treatment strategies were limited to local therapies, like surgical resection and radiotherapy, the latter in the form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 136 publications
0
1
0
Order By: Relevance
“…Nevertheless, this finding suggests that some PPMM patients may respond well to BRAF-targeted therapy ( 25 ). Immunotherapy is mainly used to treat patients with multiple melanoma brain metastases, with drugs like ipilimumab and pembrolizumab shown to be effective ( 37 ). Famoso et al reported a case of a PPMM with positive PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this finding suggests that some PPMM patients may respond well to BRAF-targeted therapy ( 25 ). Immunotherapy is mainly used to treat patients with multiple melanoma brain metastases, with drugs like ipilimumab and pembrolizumab shown to be effective ( 37 ). Famoso et al reported a case of a PPMM with positive PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…WBRT that spares the hippocampus, which affects cognitive function, through the use of intensity-modulated radiation therapy and other modalities, has become the treatment of choice [26]. However, some clinical scenarios still require classical 3DCRT, such as in cases with a short prognosis where the primary tumor or intracranial lesions have become uncontrollable due to lack of response to chemotherapy [27], or when the neurological findings due to BMs are urgent. One of the significant findings of this study is that WBRT using older 3DCRT technology remains a viable option for treating BMs at the initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%